Hubungan Strong Madden-Jullian Oscillation (MJO) Terhadap Kecepatan Angin dan Suhu Permukaan Laut (SPL) di Perairan Indonesia - Pande Ketut Cahya Krisnanta Arioka; I Wayan Gede Astawa Karang; Gede Surya Indrawan (Journal of Marine Research and Technology, 2022)
Madden–Julian Oscillation (MJO) is a large-scale ocean-atmosphere phenomenon that occurs due to strong atmospheric circulation patterns and convection from Indonesian Seas then moves eastward (Pacific Ocean) with an average speed of 5 m/s. MJO is categorized into strong MJO and weak MJO whose occurrences can be identified by Outgoing Longwave Radiation (OLR). Strong MJO also has a relationship with wind and Sea Surface Temperature (SST), so that MJO events affect wind and SST. Studies on strong MJO have been conducted but in a short period, narrow research area, and only one related variable, namely the relation between MJO and precipitation The purpose of this study is understanding the relation between MJO with wind speed and SST in Indonesian Seas for the period 2003 - 2020. The data used are carried out using remote sensing technology. The research data was conducted using filtered, then analyzed by the Hovmöller diagram, and finally analyzed by correlation analysisThe research area, namely the Indonesian Seas, consists of regions A (Western Sea of Sumatera), region B (North Java Sea), region C (Southern Sea of Java), region D (Sulawesi Sea), region E (Banda Sea), region F (Aru Sea), and region G (North Papua Sea). The results of the study show that there is a relationship between OLR, wind speed, and SST where the relation between OLR and wind speed gets mostly fluctuating values, where there are negative values as well as positive values, and the relation between OLR and SST is inversely proportional.